Changes in the Use of Non-nutritive Sweeteners in the Chilean Food and Beverage Supply After the Implementation of the Food Labeling and Advertising Law - Zancheta Ricardo, Camila; Corvalán, Camila; Smith Taillie, Lindsey; Quitral, Vilma; Reyes, Marcela (Frontiers in Nutrition, 2021)
Reductions on the sugars content of the food supply have been described after the initial implementation Chilean Labeling Law, but it is unclear if sugars were replaced by non-caloric sweeteners (NNS). We evaluated changes in the NNSs use in foods and beverages after the initial implementation of the labelling law. We used longitudinal data on packaged foods and beverages collected in six major supermarkets and three candy distributors in Santiago, Chile, in January–February 2015/2016 and in January–February 2017. We included in the analysis beverages, dairy-based beverages, yogurts, breakfast cereals, desserts and ice creams, candies and sweet confectioneries, and sweet spreads with a market share ≥ 1% of their food groups (n=999). We compared the use of any NNS, the number of different NNSs used, and the combined use of NNSs and ingredients adding sugars using nonparametric tests for matched samples. We evaluated the association between a reduction in sugars and starting NNS use in the postimplementation period using negative binomial regression. The use of any NNS increased from 37.9% to 43.6% (p<0.001 after the law’s implementation, NNSs increased among beverages, dairy-based beverages, yogurts, and desserts and ice creams (p<0.05), driven mostly by increases in sucralose and stevia use (p<0.05)). We found that reformulated products that reduced the amount of sugars below the law’s cutoff were more likely to start using an NNS in the postimplementation period (prevalence ratio: 12.1; 95%CI: 7.2–20.2; p<0.001). Our results suggest that NNSs likely replaced sugars after the initial implementation of the law. Further analyses should explore how these changes may impact NNS consumption.